Suicide and Emo youth subculture : a case analysis - Definis-Gojanović, Marija (Array, 2009)
Summary: Depression and suicide present a serious health problem especially for teenagers as they are increasingly diagnosed with mood disorders of different severity, possibly leading to suicidal activity. Reported here is a misfortunate young girl who committed suicide by jumping from high altitude. She left a suicide note which, together with her behavior in the death-preceding period, pointed to her apparently belonging to an Emo subculture. Although few and scarce, most existing articles and reports on Emo subculture found that its members like to focus on negative things, dark premonitions and deprivation of enjoyment, like self harm and suicide but no scientific information are available about the characteristics, trends and possible suicidal tendencies of children and adolescents who belong to this subgroup. It is for the future researches to answer whether this type of behavior and music preference are causal factors for increased suicidal vulnerability, or personal characteristics and anamnesis, upbringing and mental health status are actual sources of the problem